Human bocavirus 1 coinfection is associated with decreased cytokine expression in the rhinovirus-induced first wheezing episode in children - Hurme Pekka; Sahla Reetta; Rückert Beate; Vahlberg Tero; Turunen Riitta; Vuorinen Tytti; Akdis Mübeccel; Söderlund-Venermo Maria; Akdis Cezmi; Jartti Tuomas (John Wiley and Sons Inc, 2025)
Background
Rhinovirus (RV)-induced first wheezing episodes in children are associated with a markedly increased risk of asthma. Previous studies have suggested that human bocavirus 1 (HBoV1) may modify RV-induced immune responses in young children. We investigated cytokine profiles of sole RV- and dual RV-HBoV1-induced first wheezing episodes, and their association with severity and prognosis.
Methods
Fifty-two children infected with only RV and nine children infected with dual RV-HBoV1, aged 3–23 months, with severe first wheezing episodes were recruited. At acute illness and 2 weeks later, peripheral blood mononuclear cells were isolated, and stimulated with anti-CD3/anti-CD28 in vitro. Multiplex ELISA was used to quantitatively identify 56 different cytokines at both study points. Patients were prospectively followed for 4 years.
Results
The mean age of the children was 14.3 months, and 30% were sensitized. During the acute illness, the adjusted analyses revealed a decrease in the expression of IL-1b, MIP-1b, Regulated upon activation, normal T cell expressed and presumably secreted (CCL5), TNF-a, TARC, and ENA-78 in the RV-HBoV1 group compared with the RV group. In the convalescence phase, the RV-HBoV1 group was characterized by decreased expression of Fractalkine, MCP-3, and IL-8 compared to the RV group. Furthermore, the hospitalization time was associated with the virus group and cytokine response (interaction p < 0.05), signifying that increased levels of epidermal growth factor and MIP-1b were related with a shorter duration of hospitalization in the RV-HBoV1 coinfection group but not in the RV group.
Conclusions
Different cytokine response profiles were detected between the RV and the RV-HBoV1 groups. Our results show the idea that RV-induced immune responses may be suppressed by HBoV1.